Transfer effects in auditory temporal preparation occur using an unfilled but not filled foreperiod. Issue 8 (August 2021) - Crowe, Emily M; Los, Sander A; Schindler, Louise; Kent, Christopher
How quickly participants respond to a "go" after a "warning" signal is partly determined by the time between the two signals (the foreperiod) and the distribution of foreperiods. According to Multiple Trace Theory of Temporal Preparation (MTP), participants use memory traces of previous foreperiods to prepare for the upcoming go signal. If the processes underlying temporal preparation reflect general encoding and memory principles, transfer effects (the carryover effect of a previous block's distribution of foreperiods to the current block) should be observed regardless of the sensory modality in which signals are presented. Despite convincing evidence for transfer effects in the visual domain, only weak evidence for transfer effects has been documented in the auditory domain. Three experiments were conducted to examine whether such differences in results are due to the modality of the stimulus or other procedural factors. In each experiment, two groups of participants were exposed to different foreperiod distributions in the acquisition phase and to the same foreperiod distribution in the transfer phase. Experiment 1 used a choice-reaction time (RT) task, and the warning signal remained on until the go signal, but there was no evidence for transfer effects. Experiments 2 and 3 used a simple- and choice-RT task, respectively, and there was silence between the warning and go signals. Both experiments revealed evidence for transfer effects, which suggests that transfer effects are most evident when there is no auditory stimulation between the warning and go signals.